Japanese economic cooperation in the Asia-Pacific Region and Japanese foreign direct investment in the Philippines since 1980s - Morisawa, Keiko (1992)
The purpose of this paper is to investigate the impact of Japanese economic cooperation on the Philippine economy, especially the impact of Japanese direct investment in the Philippines since the mid 1980s. First, a broad discussion on the changing characteristics of Japanese economic cooperation in the Asia-Pacific region is presented. The discussion then focuses on the characteristics of Japanese direct investment in the Philippines since the mid-1980s and assesses its impact on Philippine industrialization. In conclusion, the paper explores the nature of Japanese-Filipino economic cooperation.
Keywords: Investments, Japanese -- Philippines